Menuju Rumah Sakit Tangguh Bencana Berbasis Komunitas - Stephanus Maria Eduat; Johan Danu Prasetya; Tedy Agung Cahyadi; Yohana Noradika Maharani; Widyawanto Prastistho; Yohanes Ary Prayoga; Bambang Dwijo Pranowo; Ficky Adi Kurniawan (Jurnal Anestesi, 2025)
The hospital is the end of service for victims affected by disasters, the frequency and intensity of disasters that continue to increase give great responsibility to the hospital in reducing the rate of injury and even death so that the resilience of the hospital must be bouncy by maximizing all related elements. However, there is growing evidence that many hospitals are vulnerable to disasters, and more effective strategies are needed to minimize disaster risk. This paper uses the method of narrating a literature review with a simple process hierarchy analysis approach to see the priorities of implementing resilience in hospitals. The result of this paper is that hospital resilience will be able to increase by involving the community, both internal and external, by adopting good practices for community-based disaster risk management.